Isolamento e identificação de fungos filamentosos em dentes com indicação de retratamento - Victor, Fernanda Loretti (2009)
The aim of the present study was to isolate and identify filamentous fungi from root canals of teeth with failed root-canal treatment. Thirty root-filled teeth with periapical lesions were selected for this study. A detailed medical and dental history was obtained from each patient. All patients signed informed consent to participate. The root-filling material was removed without the use of chemical solvents and after that the root canals were sampled using 3 sterile paper points for each tooth. The paper point samples from the root canal were transferred to a tube with Saboraud Dextrose Agar medium plus cloranfenicol to avoid bacterial growth. The specimens were collected in isolated camp by two fire lamps. The same procedure was done with all the samples. The tubes were maintained in ambient temperature for 7 to 14 days observing the colony growth. The isolated material was sent to Mycology Laboratory at the Oswaldo Cruz Institute to micromorphologic identification in genus and species. Filamentous fungi grew in 3 of the 30 teeth (10%). Those teeth belong to immunodepressed patients. The species were identified: Aureobasidium pullulans, Aspergillus niger e Penicilium glabrum.